Epidermoid renal cyst - An unusual case report and review of literature (Indian Journal of Case Reports, 2018)
Epidermoid cyst in the kidney is an exceptionally rare entity. Only a few cases have been reported. The aim of reporting this case is to highlight its rarity and to create awareness of the entity as a differential diagnosis of cysts in the kidney. We report a case of a 37-year-old lady who presented with loin pain of 1 year duration. Imaging studies revealed hydroureteronephrosis with multiple calculi and a cyst in the kidney. Histological examination revealed epidermoid cyst.